(untitled) (Journal of the College of Basic Education, 2023)
The current research aims to identify the effect of the proactive evidence strategy on reading comprehension and visual thinking among first-grade intermediate students. To achieve this, the researchers adopted an experimental design located in the field of experimental designs with partial control, and a final test for the two research groups, one experimental and the other a control one. The researchers chose randomly (Hammurabi intermediate school for boys ) located in Shubar district, the center of Babil Governorate, and in the same way, Division (A) was chosen to represent the control group of thirty-five students, and Division (B) to represent the experimental group of thirty-three students. They prepared teaching plans for teaching the two research groups and presentation Two of them are based on a group of experts and specialists to know their validity and suitability for first-grade students. The article prepared a test for visual thinking consisting of five sections and twenty-five test items of the multiple choice type, and after analyzing Results Statistically, the two researchers concluded: The students of the experimental group outperformed the students of the control group in reading comprehension, and there were no differences between the students of the experimental group that studied reading material using the proactive evidence strategy and the students of the control group that studied the same material in the traditional way in the visual thinking test, and in the light of From these results, the researchers recommended a set of recommendations, including the need to use the proactive evidence strategy in teaching reading; Because of its positive impact on improving student learning, and training teachers of the Arabic language in the intermediate stage on modern strategies in teaching to develop the ability to understand the reading, including the proactive guide strategy. To identify the impact of the proactive evidence strategy in improving the teaching of other branches of the Arabic language, such as grammar or rhetoric.Keywords: proactive evidence strategy, reading comprehension, visual thinking.